2001
DOI: 10.1021/ja017043f
|View full text |Cite
|
Sign up to set email alerts
|

Radical Cation-Mediated Annulation. Stereoselective Construction of Bicyclo[5.3.0]decan-3-ones by Aerobic Oxidation of Cyclopropylamines

Abstract: rings with 7 or more members rings with 7 or more members Q 0050 -085Radical Cation-Mediated Annulation. Stereoselective Construction of Bicyclo[5.3.0]decan-3-ones by Aerobic Oxidation of Cyclopropylamines.-Intramolecular Kulinkovich cyclopropanation of olefin-tethered amides such as (I) and (VII) followed by tandem ring expansion-cyclization of the resulting bicyclic aminocyclopropenes offers a stereocontrolled method to prepare bicyclo[5.3.0]decan-3-ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…9 In this system, CAN and bromide are soluble in the aqueous phase, whereas the cyclopropyl alcohol is only soluble in the organic phase leading to selective oxidation of the bromide ion. This solvent milieu provided isolated yields of β-bromo products in the range of 71-92% (entries 4,8,12,16).…”
mentioning
confidence: 99%
“…9 In this system, CAN and bromide are soluble in the aqueous phase, whereas the cyclopropyl alcohol is only soluble in the organic phase leading to selective oxidation of the bromide ion. This solvent milieu provided isolated yields of β-bromo products in the range of 71-92% (entries 4,8,12,16).…”
mentioning
confidence: 99%
“…[6] We anticipated that electrochemical methods such as cyclic voltammetry and preparative electrolyses would be tools of choice to gain better insight in this reaction and could lead to the design of a more general and environmentally friendly experimental procedure. [7] For the purpose of this study, aminocyclopropanes 1 a-e, 2 a,b, 3, and 4 were prepared by using intra-or intermolecular Kulinkovich-de Meijere reactions, [8] following a modification Scheme 1. Autocatalytic aerobic oxidation of aminocyclopropanes to aamino endoperoxides.…”
mentioning
confidence: 99%
“…One-electron reduction could then form the stable (ferrous) MIC complex shown in Figure 7. Precedent for this suggestion can be found in a review by Lindeke [58] which suggested that a structure analogous to 21 (i.e., R = PhCH 2 -, R' = Ph, but with H replacing EnzFe) could undergo decomposition to form benzaldehyde, water and α-nitrosotoluene (PhCH 2 NO) as a precursor to benzaldoxime (2). Further precedent comes from work of Sang et al who showed that alkylhydroperoxy radicals (ROO•) add to the spin-trap reagent C-phenyl-N-tert-butyl nitrone (PBN) to form unstable adducts resembling structure 21…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is supported by direct observations of ring-opened products in chemical model systems [2][3][4][5], and in the oxidation of cyclopropylanilines by peroxidases [6][7][8]. While the formation of cinnamaldehyde as a metabolite of an N-(2-phenylcyclopropyl)amine has been reported, direct evidence for the formation of ring-opened metabolites of a simple N-cyclopropylamine has not been demonstrated for a P450 system.…”
Section: Introductionmentioning
confidence: 94%